Analysis of Improving Teacher Discipline in Teaching by Superviing the Head of Madrasah MTs Bukhari Labuhanbatu - Dwina Putri; Anggili Pratama; Suryatik Suryatik; Ali Sadikin Ritonga; Santi Erika (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to reveal how "Increasing Teacher Discipline in Teaching by Supervising the Madrasah Principal of MTs Al Bukhari Labuhanbatu" This research uses qualitative research, with direct research into the field. The data collection techniques used by researchers were interviews and observations with teachers and documentation carried out by researchers in the field in order to strengthen the validity of the research data. So the researcher mastered the four standard validation approaches consisting of: 1) credibility, 2) transferability, 3) dependability. Firmness to classify data, data that has been obtained from research results. The findings include four findings: 1) Managerial supervision at MTs Al Bukhari Labuhanbatu has been carried out properly and in accordance with the goals and roles of the manager himself, 2) The discipline of teachers in these Madrasas is included in the disciplined category from various aspects, especially seen from the teacher himself from the level of attendance already it is very rare to find teachers who come to school late and are on time to start learning and are disciplined in preparing learning tools, 3) the driving and inhibiting factors for teacher discipline in Madrasas are almost all the information that researchers get that there are two factors, namely from the individual himself (internal) and from leaders, co-workers or other demands (external) and 4) Managerial supervision in improving teacher discipline at MTs Al Bukhari Labuhanbatu has very good implications, with the supervision carried out by the Head of Madrasah towards teachers, teachers feel loyal p his work carefully and with a sense of responsibility because he feels he is being watched.